ON SPECIFIC ISSUES OF PROMOTION OF HEALTHY NUTRITION IDEAS BY RESTAURANT ESTABLISHMENTS THROUGH PUBLIC RELATIONS PRACTICES - Мамченко, Людмила; Нєміріч, Олександра; Кузьмін, Олег (SWorldJournal, 2025)
The paper examines the issue of promoting healthy eating ideas by restaurant establishments using public relations practices. The modern restaurant industry is characterized by an extremely high level of competition, dynamics, and dependence on changes in